Exhaled nitric oxide in acute exacerbation of pediatric asthma - Ratnawati Ratnawati; V Nguyen; J Morton; R L Henry; P S Thomas (Indonesian Pediatric Society Publishing House, 2008)
Background Measurement of exhaled nitric oxide (eNO) is a non- invasive and easy method to monitor airway inflammation. Objectives To compare the levels of eNO during and after an exacerbation of asthma, to evaluate the effect of glucocor- ticosteroids (GCS) on the levels of eNO and to correlate eNO with other markers of inflammation such as symptom scores, FEV 1 and sputum eosinophils. Methods The observational study was performed over 24 months at a tertiary paediatric hospital. Subjects underwent eNO measurement, spirometry and sputum induction during an asthma exacerbation and then two weeks later. A symptom score was recorded everyday for two weeks. All subjects were treated with ß 2 -adrenergic agonists and an oral glucocorticosteroid (GCS). Results Fifteen subjects with acute asthma exacerbation aged 5 and 16 years old participated in the study. The mean level of eNO during the acute exacerbation was significantly higher than eNO levels at the follow-up visit, 11.2 (95%CI 9.2;13.2) vs. 8.0 (95%CI 5.0;11.1) ppb, P=0.03. In the acute exacerbation, eNO correlated with sputum eosinophils (P=0.04), but no correlation could be found between eNO and the other markers of inflammation during exacerbation or follow up. Conclusions eNO level increased during asthma exacerbation and decreased after two weeks of glucocorticosteroid therapy. Measurement of eNO is a practical monitoring method in emergency management of asthmatic children.